2016
DOI: 10.1097/ccm.0000000000001871
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Ventilator-Associated Events Reported to the National Healthcare Safety Network in 2014*

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 26 publications
(34 reference statements)
3
64
3
1
Order By: Relevance
“…5 Although VAE reporting is not mandated, 36 BICUs reported data to the NHSN in 2014 with a pooled mean incidence of 6.55 VAE/1,000 ventilator days and a pooled mean incidence of IVACs (including possible VAP) of 2.93 events/1,000 ventilator days. 6 We found an incidence of VAE-possible VAP cases ranging from 0.6 to 1.0/1,000 ventilator days over a 4.5-year period, which was much lower than our pre-2013 VAP rates. Even though the BICU is our highest risk unit for VAP, we found very few events that met the current VAE-possible VAP definition.…”
Section: Discussioncontrasting
confidence: 63%
“…5 Although VAE reporting is not mandated, 36 BICUs reported data to the NHSN in 2014 with a pooled mean incidence of 6.55 VAE/1,000 ventilator days and a pooled mean incidence of IVACs (including possible VAP) of 2.93 events/1,000 ventilator days. 6 We found an incidence of VAE-possible VAP cases ranging from 0.6 to 1.0/1,000 ventilator days over a 4.5-year period, which was much lower than our pre-2013 VAP rates. Even though the BICU is our highest risk unit for VAP, we found very few events that met the current VAE-possible VAP definition.…”
Section: Discussioncontrasting
confidence: 63%
“…Edwards et al [7] found that VAP prevalence in PICUs in the USA was 0%-3.2% in both 2006 and 2007. Magill et al [4] reported that VAP prevalence was 6.89-8.79 patients per 1,000 ventilator days. In Turkey, the National Surveillance report of 2015 estimated VAP prevalence in PICUs as 4.7 patients per 1,000 ventilator days [8].…”
Section: Discussionmentioning
confidence: 99%
“…Prior antibiotic use, application of invasive procedures, use of drugs affecting gastric empty-ing and pH, aspiration of gastric contents, prolonged mechanical ventilation, patient position, severity of underlying illness; central nervous system disorders, frequent changes of endotracheal tubes, and presence of coma, pneumonia, and acute respiratory distress syndrome are among the factors predicting VAP development [3]. VAP is an important cause of morbidity and mortality in patients in the ICU [4].…”
Section: Introductionmentioning
confidence: 99%
“…Ventilator‐associated pneumonia (VAP) is the most common severe infectious complication of mechanical ventilation; reported incidences range from 1·2 to 18·3 episodes per 1000 days of mechanical ventilation, varying depending on the study population, the definition used for the diagnosis (Magill et al, ; Skrupky et al, ) and the preventive measures applied in the reporting intensive care unit (ICU) (Álvarez Lerma et al, ; Sinuff et al, ). Likewise, the mortality attributable to VAP varies widely, initially ranging from 33% to 50%, although recent studies have reported much lower values, ranging from 6% to 13% (Melsen et al, ; Melsen et al, ; Timsit et al, ).…”
Section: Introductionmentioning
confidence: 99%